An omentum-cultured 3D-printed artificial trachea: in vivo bioreactor. (12th November 2018) - Park, Hae Sang; Lee, Ji Seung; Jung, Harry; Kim, Do Yeon; Kim, Sang Wook; Sultan, Md. Tipu; Park, Chan Hum
Abstract: The purpose of this study was to evaluate whether the prior implantation of a 3D-printed polycaprolactone (PCL) artificial trachea in the omentum is beneficial for revascularization of the scaffold and reduces associated complications in the reconstruction of a circumferential tracheal defect. Ten New Zealand rabbits were divided into 2 groups: (1) PCL-OC group (PCL scaffold cultured in omentum for 2 weeks before transplantation) and (2) PCL group. In the PCL-OC group, newly formed connective tissue completely covered the luminal surface of the scaffold with mild inflammation at 2 weeks postoperatively; a minor degree of stenosis was noted at 8 weeks postoperatively. The PCL group showed scaffold exposure without any tissue regeneration at 2 weeks postoperatively, and a moderate degree of luminal stenosis 6 weeks after implantation. Histology revealed highly organized regenerated tissue composed of ciliated respiratory epithelium, and submucosal layer in the PCL-OC group. Neo-cartilage regeneration was noted in part of the regenerated tissue. The PCL group demonstrated severe inflammation and an unorganized structure compared to that of the PCL-OC group. In vivo omentum culture of the tracheal scaffold before transplantation is beneficial for rapid re-epithelialization and revascularization of the scaffold. It also prevents postoperative luminal stenosis.